Comparison of Labor Duration by Parity Among Mothers at Rizki Clinic, Medan Tembung District - Ribur Sinaga; Sari Khowajan Tondang; Eva Ratna Dewi; Marliani; Ali Imran Sirait; Dyanti SR Butarbutar (Asosiasi Dosen Muda Indonesia, 2026)
Prolonged labor remains an important clinical issue because it can increase maternal fatigue and the risk of complications during delivery. Parity is known to influence the progress of labor, yet stage-specific evidence comparing primiparous and multiparous mothers in primary care settings is still limited. Understanding these differences is essential to improve intrapartum monitoring and maternal support. Objective: This study aimed to compare labor duration between primiparous and multiparous mothers at Rizki Clinic, Medan Tembung District, and to identify which stages of labor contribute most to the observed differences. Method: This study employed a quantitative observational analytic approach with a cross-sectional design conducted from April to July 2024. The sample consisted of 30 mothers (15 primiparous and 15 multiparous) selected using predetermined inclusion and exclusion criteria. Data on labor duration were obtained through direct observation and medical records. Descriptive analysis and the Mann–Whitney U test were used to examine differences between groups. Findings: The overall mean labor duration was longer in primiparous mothers (10.60 hours) compared with multiparous mothers (5.13 hours). Stage-specific analysis showed a significant difference in the first stage (Kala I), with primiparous mothers averaging 10.24 hours (7–11 hours 30 minutes) and multiparous mothers 6.5 hours (4–8 hours 45 minutes) (p = .000). No statistically significant differences were found in the second stage (mean 19 vs 15 minutes; p = .065) or the third stage (mean 10 vs 7 minutes; p = .086). Implications: The findings highlight the importance of focused monitoring and supportive care during the first stage of labor, particularly for primiparous mothers, to reduce anxiety and prevent prolonged labor. The results can inform clinical practice in primary care settings to improve labor management strategies. Originality/Value: This study provides stage-based comparative evidence on labor duration using clinic-level data, offering practical insight into parity-related differences and contributing to improved intrapartum care planning.